Modelo estructural sostenible comparando tipologías de construcciones antiguas versus actuales en el sector Chingazo Alto, Ela y Valparaíso del Cantón Guano - Coral Morocho, Johana Elizabeth (2021)
ABSTRACT: This document is an exploratory investigation, whose writing has been possible through the collaboration of several entities such as the “Universidad Nacional de Chimborazo”, ECOSUR and the “Instituto Nacional de Patrimonio Cultural” Zone 3 (INPC-Z3), which work in Guano, where several projects are carried out jointly with the communities and whose experiences and related documents have contributed to this investigation; At present, many institutions, like these, seek the relationship of the environment with the individual in general, by optimizing spaces, reducing pollution, generating materials, all this trying to maintain a focus on the most economically vulnerable groups, while sustainable development is sought, these being important terms in personal and collective development. The objective of the investigation has been the elaboration of a structural model that is inclusive in the Ela, Valparaíso and Chingazo Alto Guano sectors, considering relevant aspects to its culture and social identity, environmental factors derived from the materials of the place and construction processes, to try to reduce the economic impact within the construction processes and make it structurally viable. The collection of information was carried out through the cooperation of the INPC-Z3 through the SIPCE system, observation in field visits and collection of experiences and documentation with ECOSUR and previous investigations in the area. The identification and comparison between construction systems has been important to generate indicators and guidelines for consideration for the proposal of the final model whose cultural, social, environmental and structural combination is relevant to the study area. In the landscapes of these Guano rural sectors, it is common to observe vestiges of vernacular dwellings, self-supporting wooden structures, sharing spaces with traditional old dwellings, wooden or wattle and daub and finally current steel or concrete dwellings. The comparison between these systems has generated a series of useful indicators for a composition of a mixed model, which itself is related to the spaces that are consistent with the lifestyle of the sector, both of vernacular and traditional and current constructions. Likewise, a configuration can be represented according to the construction system, variable to the rectangular one usually occupied in the urban sector; the development of activities not only internal to the dwelling creates configurations dependent on central courtyards or combined social zones external and internal to the main dwelling. Finally, for the proposal, it has been tried to maintain the traditional structure in Eucalyptus wood and bahareque masonry that creates a lightened structure, all this in relation to the social and development spaces in the area such as orchards and workshops; All this, to show that the structure is not only limited to being a functional solution, but rather, giving each construction system a purpose of connection with each space. The term sustainable encompasses a wide range of possibilities, but likewise, it is imperative to complement these proposals with a sustainable plan for the exploitation of wood as a construction material; Likewise, social and cultural identity should not be relegated to constructions above the industrialization of construction processes. A balance between the social, environmental and functional, can generate a change of mentality in the current construction, since there are no participatory plans for the conservation of heritage, so it is necessary to start observing it as an opportunity for sustainable development instead of allocating the subject to its deterioration and eventual disappearance.